Fusiform Anastomosis Technique with a Single Longitudinal Incision in the Lacrimal Sac in External Dacryocystorhinostomy - Ucar, Fikret; Tezel, Zafer (Klinische Monatsblätter für Augenheilkunde, 2022)
Background In the present study, we aimed to evaluate the surgical outcomes of the fusiform anastomosis technique in external dacryocystorhinostomy (ex-DCR) that we designed in the form of a physiological tube, which sufficiently covered the bone ostium with the mucosa.Material and Methods This was a retrospective observational study that included 145 eyes of 131 patients who underwent ex-DCR due to nasolacrimal duct obstruction. The patients were divided into two groups. Group 1 included 73 eyes of 65 patients who underwent fusiform anastomosis, and group 2 included 72 eyes of 66 patients who underwent conventional anterior and posterior flap anastomosis. The open nasolacrimal passage with lacrimal irrigation and the absence of reflux were accepted as anatomical success, and the absence of epiphora symptoms was accepted as functional success. The groups were compared in terms of anatomical success, functional success, and granulation tissue formation.Results Anatomical success was observed in 73 eyes (100%) in group 1 and 66 eyes (91.6%) in group 2 (p = 0.01). Functional success was observed in 72 of 73 eyes (98.6%) in group 1 and 65 of 72 eyes (90.2%) in group 2 (p = 0.02). Nasal endoscopic examination performed in 32 eyes in group 1 and 28 eyes in group 2 revealed that granulation tissue was observed in 7 of 28 eyes (25%) in group 2, while there were no eyes with granulation tissue in group 1 (p = 0.01).Conclusion The fusiform anastomosis technique in ex-DCR provided excellent anatomical success and extremely good functional success.
Keywords: nasolacrimal duct obstruction; external DCR with fusiform anastomosis; reobstruction; anterior and posterior flap anastomosis; oculoplastic